CASE STUDY: MENGURANGI VERTIGO PADA PENDERITA BENIGN PAROXYSMAL POSITIONAL VERTIGO (BPPV) DENGAN METODE SEMONT LIBERATORY MANEUVER DAN BRANDT DAROFF EXERCISE - Renni Hidayati Zein; Talitha Samntha Zada (Jurnal Ilmiah Fisioterapi, 2024)
ABSTRACT Bacground: Benign paroxysmal positional vertigo (BPPV) adalah is a vestibular disorder that often caused perifer vertigo caused by a sudden change in head position. BPPV is manifested by spinning and shifting dizziness in addition to nausea, vomiting, cold sweat, nystagmus, and balance issues when the position of the head shifts against gravity as a result of adhesions or floating calcium carbonate crystals or otoliths in the semicircular canals, a condition known as vertigo occurs. Purpose: The goal of this study was to evaluate the efficiency of physiotherapy treatment for reducing vertigo in BPPV patients utilizing the semont liberatory maneuver and brandt baroff exercise. Research Method : A case study that is presented as a descriptive narrative is the research approach that was chosen. Research subjects consisted of a single benign paroxysmal positional vertigo (BPPV) specimen that met the specimen acceptance criteria. The study was carried out 6 times in therapy at the FIT Centrum, Aesthetic, Sport, Rehab Center & Food Pekanbaru clinic. Assessment with the vertigo symptom scale-short form (VSS-SF) measurement tool revealed a reduction in vertigo symptoms compared to the VSS-SF total score, i.e. from 27 to 14. Result: : Based on the results of this study, it can be concluded that the semont liberatory maneuver and brandt daroff exercise can help patients with benign paroxysmal positional vertigo (BPPV) reduce symptom and recurrence of vertigo.